Rancang Bangun Sistem Informasi Administrasi Surat Desa Berbasis Web Dengan Qr Code Dan Tracking Status Menggunakan Metode WaterfallDi Desa Tuhemberua Ulu - Niko Demus Baru Zebua; Nethania Nonifati Roselin Gea; Jurisman Waruwu (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Letter administration services in villages still largely rely on manual processes, causing slow service, recording errors, archive search difficulties, and a lack of transparency regarding application status. This study aims to design and build a web-based village letter administration information system equipped with QR Code validation and real-time tracking status, using the Waterfall development method, for Tuhemberua Ulu Village. The development stages consist of requirements analysis, system design, implementation, testing, and maintenance. The system was built using PHP, MySQL, and Bootstrap, and tested using Black Box Testing. The results show that the system successfully manages incoming and outgoing letters, generates QR Codes to validate letter authenticity, and provides a tracking feature that allows the public to monitor the progress of their letter requests without visiting the village office. It is concluded that the developed system improves the effectiveness, efficiency, transparency, and accountability of village letter administration services compared to the previous manual system.